Harmonisasi Hukum Internasional dan Praktik Negara Dalam Sengketa Batas Laut : Studi Kasus Indonesia dan Malaysia - Kayla, Syafa Ananda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The issue of maritime boundaries between countries is a complex issue in international law, which requires harmony between international legal norms and practices applied by countries. This study analyzes the application of the United Nations Convention on the Law of the Sea (UNCLOS) 1982 in resolving maritime boundary conflicts between Indonesia and Malaysia. Using a normative legal approach, case studies, and comparative analysis, this study identifies obstacles to the implementation of international law at the national level and examines the conflict resolution mechanisms that have been used by both countries. The findings indicate that the bilateral negotiation approach remains the dominant strategy, although third-party participation and international arbitration options have their own relevance. This study offers policy recommendations that encourage sustainable peaceful resolution within the framework of international law.